Literature Review: Characteristics Of Outer Ear Diseases - Nurul Hidayah; Hermiaty Nassaruddin; Samsi Mesi (Jurnal EduHealth, 2024)
Introduction: The ear is a human organ that functions as a hearing tool. The ear consists of the outer, middle and inner parts. The structure of the outer ear consists of the earlobe (auricle) and ear canal. The external ear (EE) is anatomically and functionally divided into the cartilaginous auricle, or pinna, and the external auditory canal (EAC). The outer ear can be affected by a variety of conditions, including congenital abnormalities, trauma, inflammatory conditions (infectious or other), blood vessel abnormalities, and neoplasms (benign or malignant). Objective: This literature aims to examine the characteristics of external ear diseases. Method: This research uses a literature review method with the Preferred Reporting Items for protocol Systematic Reviews & Meta-Analyses (PRISMA). Scientific articles or journals are downloaded from PubMed, Garuda Portal, and Google Scholar with SINTA IV and V standards in the time period 20 19-2023. The keywords in this article search were characteristics, external ear disease, 853 articles were obtained in the search results. All articles were selected based on the inclusion criteria, resulting in 9 research articles that would be reviewed. Results: In the literature this was found namely 9 research articles that report the characteristics of external ear diseases consisting of congenital abnormalities, namely preauricular fistula, microtia, acquired abnormalities, namely hematoma, perichondritis, pseudocyst, ear canal abnormalities, namely cerumen, otitis externa and otomycosis. Conclusion: Characteristics of external ear diseases consist of congenital abnormalities, namely preauricular fistula, microtia, acquired abnormalities, namely hematoma, perichondritis, pseudocyst, ear canal abnormalities, namely cerumen, otitis externa and otomycosis.